Решите пожалуйста! 1)X(квадрат)-7x+12/x-2=3x(квадрат)-13x+4 2)x(квадрат)-7х+12/х-3=х(квадрат)-х-7 3)4х(квадрат)+29х+45/4(х-1)квадрат=(х+1)(х+5)/х(квадрат)-3х+2

Решите пожалуйста! 1)X(квадрат)-7x+12/x-2=3x(квадрат)-13x+4 2)x(квадрат)-7х+12/х-3=х(квадрат)-х-7 3)4х(квадрат)+29х+45/4(х-1)квадрат=(х+1)(х+5)/х(квадрат)-3х+2
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{x^2-7x+12}{x-2}=3x^2-13x+4 \\ \\ x \neq 2 \\ [/latex] Разложим на множители: а) x²-7x+12=0 D=49-48=1 x₁=(7-1)/2=3 x₂=(7+1)/2=4 x² -7x+12=(x-3)(x-4) b) 3x² -13x+4=0 D=169-48=121 x₁=(13-11)/6=2/6=1/3 x₂=(13+11)/6=4 3x² -13x+4=3(x-1/3)(x-4)=(3x-1)(x-4) [latex] \frac{(x-3)(x-4)}{x-2}=(3x-1)(x-4) \\ (x-3)(x-4)=(x-2)(3x-1)(x-4) \\ (x-3)(x-4)-(x-2)(3x-1)(x-4)=0 \\ (x-4)(x-3-(x-2)(3x-1))=0 \\ (x-4)(x-3-(3x^2-6x-x+2))=0 \\ (x-4)(x-3-(3x^2-7x+2))=0 \\ (x-4)(x-3-3x^2+7x-2)=0 \\ (x-4)(-3x^2+8x-5)=0[/latex] [latex]a) \\ x-4=0 \\ x=4 \\ \\ b) \\ -3x^2+8x-5=0 \\ 3x^2-8x+5=0 D=64-60=4 \\ x_{1}= \frac{8-2}{6}=1 \\ x_{2}= \frac{8+2}{6}= \frac{10}{6}= \frac{5}{3}=1 \frac{2}{3} [/latex] Ответ: 1;  1 ²/₃;  4. [latex] \frac{x^2-7x+12}{x-3}=x^2-x-7 \\ \\ x \neq 3 \\ \frac{(x-3)(x-4)}{x-3}=x^2-x-7 \\ x-4=x^{2}-x-7 \\ -x^{2}+x+x-4+7=0 \\ -x^{2}+2x+3=0 \\ x^{2}-2x-3=0 \\ D=4+12=16 \\ x_{1}= \frac{2-4}{2}=-1 \\ x_{2}= \frac{2+4}{2}=3 [/latex] x=3 - не подходит Ответ:  -1.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы